2017
DOI: 10.1101/225920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost evaluation during decision making in patients at early stages of psychosis

Abstract: Jumping to conclusions during probabilistic reasoning is a cognitive bias reliably observed in psychosis, and linked to delusion formation. Although the reasons for this cognitive bias are unknown, one suggestion is that psychosis patients may view sampling information as more costly. However, previous computational modelling has provided evidence that patients with chronic schizophrenia jump to conclusion because of noisy decision making. We developed a novel version of the classical beads-task, systematicall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In other words, first episode psychosis patients gathered less evidence and made hasty decisions only if they presented a lower IQ than controls. Previous studies focusing on different explanations between the JTC bias and psychotic disorders suggested that deluded patients tend to request less information because sampling itself might be experienced as more costly than it would be by healthy people 43,44 . Although patients at onset seem to adjust their strategy according to the cost of sampling where clearly stated and show more bias to sample less information in the classic task, general cognitive ability still plays an important role in their decision-making behaviour 43,44 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, first episode psychosis patients gathered less evidence and made hasty decisions only if they presented a lower IQ than controls. Previous studies focusing on different explanations between the JTC bias and psychotic disorders suggested that deluded patients tend to request less information because sampling itself might be experienced as more costly than it would be by healthy people 43,44 . Although patients at onset seem to adjust their strategy according to the cost of sampling where clearly stated and show more bias to sample less information in the classic task, general cognitive ability still plays an important role in their decision-making behaviour 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focusing on different explanations between the JTC bias and psychotic disorders suggested that deluded patients tend to request less information because sampling itself might be experienced as more costly than it would be by healthy people 43,44 . Although patients at onset seem to adjust their strategy according to the cost of sampling where clearly stated and show more bias to sample less information in the classic task, general cognitive ability still plays an important role in their decision-making behaviour 43,44 . Indeed, the inclusion of general cognitive ability in the relation between JTC and clinical status was reported to substantially decrease or nullify a prior significant association 15,26,28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…inference based on integrating observations with prior beliefs) as the cause of delusion formation (Coltheart et al, 2010;Hemsley and Garety, 1986). The notion that delusional ideation may be associated with abnormal inference has previously been related to the Jumping to Conclusions (JTC) bias in delusions (e.g., (Garety et al, 1991;Peters and Garety, 2006;So et al, 2012;Speechley et al, 2010); but see (Ermakova et al, 2017;Moutoussis et al, 2011)…”
Section: Introductionmentioning
confidence: 99%